RAD51 expression and prognostic impact in patients with stomach adenocarcinoma - Baiyu Jian; Hao Zhang; Li Fan; Yang Li; Nan Wu; Ningning Wang; Lingmin Li; Xueyan Li; Pengling Ge; Yingcai Niu; Jicheng Liu (PeerJ)
Background Stomach adenocarcinoma (STAD) is the most common gastrointestinal cancer. A clear diagnosis and molecular targeted therapy have important implications for prolonging survival of patients. RAD51 is the central catalyst of homologous recombination that plays important role in maintaining genomic integrity. However, the clinical significance of RAD51 expression in STAD patients remains unclear. This study aimed to assess the association of RAD51 expression with clinicopathological characteristics and patient outcomes. Methods In this study, RAD51 mRNA expression in STAD patients was assessed using the UALCAN and GEPIA databases. The diagnostic value of RAD51 was evaluated by analyzing the ROC curve (data from the The Cancer Genome Atlas (TCGA) database). The protein expression level of RAD51 in STAD patients and its relationship with clinicopathological characteristics and prognosis were evaluated by immunohistochemistry. Co-expression analysis of RAD51 in STAD was performed by Coexpedia and Gene Expression Profiling Interactive Analysis (GEPIA) databases. The associations of RAD51 and its co-expression genes with immune infiltrates were analyzed in TIMER database. Results Our bioinformatic analysis revealed that RAD51 demonstrates elevated expression in STAD. The ROC curve analysis yielded an AUC value of 0.9366 (95% CI [0.9075–0.9658]), confirming its potential as a biomarker for STAD. Immunohistochemical assessments validated the up-regulation of RAD51 in STAD, highlighting its significant correlation with TNM stage and T stage, but not with age, sex, grade, N stage, M stage, or P53 expression. Patients exhibiting high RAD51 expression exhibited significantly reduced overall survival. Multivariate analysis identified RAD51 expression may serve as an independent prognostic biomarker of poor prognosis in patients with STAD. Additionally, our bioinformatic analysis identified eight RAD51 co-expression genes (AURKA, CKS1B, NUSAP1, PFDN4, CCNE1, CDCA4, KIF4A, and MCM10) in STAD. Moreover, we discovered that RAD51 and its main co-expressed genes were significantly negatively associated with most or all immune cell infiltration. Conclusions RAD51 overexpression was related to disease progression and poor prognosis, as well as infiltration of immune cells in gastric cancer.